Electrochemical strategies for N-cyanation of secondary amines and α C-cyanation of tertiary amines under transition metal-free conditions. Issue 23 (9th November 2021) - Fu, Zhengjiang; Fu, Yaping; Yin, Jian; Hao, Guangguo; Yi, Xuezheng; Zhong, Tingting; Guo, Shengmei; Cai, Hu
Abstract : Electrochemical N -cyanation of secondary amines and α C -cyanation of tertiary amines have been established under transition metal-free conditions, which provide cyanamides and nitriles with good functional group tolerance from simple systems. Abstract : Transition metal-free electrochemical approaches for the N -cyanation of secondary amines and the α C -cyanation of tertiary amines have been well established, with products being obtained in moderate to good yields and with good functional group tolerance under ambient conditions. The synthetic application of the protocols has been highlighted through scale-up experiments in a galvanostatic mode. Preliminary mechanistic investigation has confirmed that TBAB played a critical role in N -cyanation transformation and has indicated that the transformation might proceed via a free radical process.